Self-care among patients enrolled in a self-monitoring blood glucose program - Vivian Saraiva Veras; Manoel Antônio dos Santos; Flavia Fernanda Luchetti Rodrigues; Clarissa Cordeiro Alves Arrelias; Tatiane Aparecida Martins Pedersoli; Maria Lúcia Zanetti
This cross-sectional study checks specific self-care activities of patients with diabetes mellitus enrolled in a self-monitoring blood glucose program from August to December 2012 in two Primary Health Care units in the interior of São Paulo, Brazil. The sample was composed of 74 female and male individuals, aged 18 years old or older. The Summary of Diabetes Self-Care Activities Questionnaire was used. It contains six dimensions: general diet, specific diet, physical activity, blood glucose monitoring, foot care, medication usage, plus three items about smoking. Eight out of the 15 self-care activities were within desirable levels, namely: healthy diet, not eating sweets, blood glucose testing and as frequently as recommended, drying between toes after washing feet, and taking medications (three items). The results enabled the identification of gaps in specific self-care activities among patients with diabetes mellitus.